The effect of the age of eggs and age of the diluent used on the quality of frozen semen - VEERAIAH, G; RAO, K BABU; NAIDU, K VENUGOPAL (The Indian Journal of Animal Reproduction, 2023)
A significant (P < 0.05) and progressive decline was recorded in percentage of post thaw motility (52.78 to 24.72); Live sperms (54.06 to 26.67) and acrosomal integrity (86.89 to69.08) in diluents constituted with increased ageof eggs (from fresh to two weeks). Similarly significant (P < 0.05) lower values were recorded in two weeks aged diluents in respect topercentage of post thaw motility (28.89), Live sperms (29.11) and acrosomal integrity (58.89)than fresh diluent, four day and one week old diluents.
Keywords: diluent used; quality of frozen semen